Long-term outcomes of catheter ablation of atrial fibrillation post-cardiac valve replacement. (15th December 2016) - Zhao, Liang; Xu, Kai; Jiang, Weifeng; Zhou, Li; Wang, Yuanlong; Zhang, Xiaodong; Wu, Shaohui; Zhang, Daoliang; Liu, Xu
Abstract: Objective: The long-term outcomes of catheter ablation of atrial fibrillation (AF) developing post-cardiac valve replacement (VR) remain undefined. Methods and results: Eighty-nine post-VR patients with AF (44% longstanding persistent AF, LSP-AF) were enrolled. Cumulative success rate of circumferential pulmonary vein ablation (CPVA for paroxysmal AF) and bidirectional block of lines and disappearance of complex fractionated atrial electrograms (CFAEs for persistent and LSP-AF) as index and repeat procedural endpoints reached 57% (mean, 1.3 procedures) during the first year, and dropped to 42% at median follow-up of 40 months (range, 24–70 months) for multiple procedures (mean, 1.6 ± 0.9 [1–5]); incidence of procedural complications was similar to that of conventional procedures. In multivariate analysis, larger right atrium (RA, 9.40 [2.64–33.36]; P  = 0.001) and rheumatic valvular disease etiology (OR, 5.49 [95% CI, 1.26–23.96]; P  = 0.023) were significant independent predictors of recurrent atrial tachyarrhythmia (ATa); in contrast, long-term freedom from ATa was comparable between single and double valve replacement groups (42.1% vs. 43.7%, P  = 0.880), or mechanical and bioprosthetic valves groups (41.7% vs. 50.0%, P  = 0.620). Conclusion: In this single-center prospective study, treatment of post-VR AF with commonly used ablation strategies including CPVA and linear and CFAE ablation had limited long-term success, with ATa recurrence risk appearing higher in the setting of RA enlargement and rheumatic valvular disease and unrelated to valves characteristics.